Partial fractions

Discussion in 'Math' started by boks, Dec 11, 2008.

  1. boks

    Thread Starter Active Member

    Oct 10, 2008
    218
    0
    \frac{s-1}{s(s-2)^2}

    How can I expand this fraction?

    \frac{A}{s} + \frac{B}{(s-2)} + \frac{C}{(s-2)^2}

    right?

    This gives me the equation

    As^3 - 6As^2 + 12As - 8A  Bs^3 - 4Bs^2 + 4Bs + Cs^2 - 2Cs = s-1

    so that

    (1) A + B =0
    (2)- 6A - 4B + C = 0
    (3) 12A + 4B - 2C = 1
    (4) -8A = -1

    (4) gives A = 1/8
    (1) gives B = -1/8
    (2) gives C = 1/4

    The correct answer is

    A = -1/4
    B = 1/4
    C = 2/4

    What's wrong?
     
    Last edited: Dec 11, 2008
  2. studiot

    AAC Fanatic!

    Nov 9, 2007
    5,005
    513
    Yes
    I make it

    A=-1
    B=+1
    C=+1
     
  3. vvkannan

    Active Member

    Aug 9, 2008
    138
    11
    I dont think you have got the equation right.
    The equation should be
    As^2-4As+4A+Bs^2-2Bs+Cs = s-1
     
  4. boks

    Thread Starter Active Member

    Oct 10, 2008
    218
    0
    Thanks, I figured it out now.
     
  5. studiot

    AAC Fanatic!

    Nov 9, 2007
    5,005
    513
    OOps

    What sloppy arithmetic Studio T

    Go to the bottom of the class.

    Boks original was correct.
     
Loading...